A Novel Lactococcal Vaccine Expressing a Peptide from the M2 Antigen of H5N2 Highly Pathogenic Avian Influenza A Virus Prolongs Survival of Vaccinated Chickens - Kaleb A. Reese; Christopher Lupfer; Rudd C. Johnson; Georgi M. Mitev; Valerie M. Mullen; Bruce L. Geller; Manoj Pastey (Veterinary Medicine International)
A cost-effective and efficacious influenza vaccine for use in commercial poultry farms would help protect against avian influenza outbreaks. Current influenza vaccines for poultry are expensive and subtype specific, and therefore there is an urgent need to develop a universal avian influenza vaccine. We have constructed a live bacterial vaccine against avian influenza by expressing a conserved peptide from the ectodomain of M2 antigen (M2e) on the surface of Lactococcus lactis (LL). Chickens were vaccinated intranasally with the lactococcal vaccine (LL-M2e) or subcutaneously with keyhole-limpet-hemocyanin conjugated M2e (KLH-M2e). Vaccinated and nonvaccinated birds were challenged with high pathogenic avian influenza virus A subtype H5N2. Birds vaccinated with LL-M2e or KLH-M2e had median survival times of 5.5 and 6.0 days, respectively, which were significantly longer than non-vaccinated birds (3.5 days). Birds vaccinated subcutaneously with KLH-M2e had a lower mean viral burden than either of the other two groups. However, there was a significant correlation between the time of survival and M2e-specific serum IgG. The results of these trials show that birds in both vaccinated groups had significantly (P<0.05) higher median survival times than non-vaccinated birds and that this protection could be due to M2e-specific serum IgG.